Experimental Study on Gas-Solid Heat Transfer Characteristics for the Vertical Waste Heat Recovery Using the Inverse Problem Method - Sizong Zhang; Zhi Wen; Yi Xing; Xunliang Liu; Hui Zhang; Yaxuan Xiong (International Journal of Photoenergy)
To establish an accurate model to optimize the vertical cooling process of the sinter, the inverse problem method is used to calculate the gas-solid heat transfer coefficient based on the gas outlet temperature, which is fitted into the correlation. The research indicates that the increase in the gas velocity is beneficial to the enhancement of the gas-solid heat transfer. With the gas velocity ug increasing from 0.8 m·s-1 to 1.6 m·s-1, the heat transfer coefficient hv increases by about twice. But this effect will weaken with the increase in the particle size. Besides, the reduction of the particle size is conducive to improving the convective heat transfer intensity between the gas and solid. With the particle size decreasing, this enhancement effect is progressively evident. At ug of 0.8 m·s-1, the increasing extent of hv is 1142.25 W·m-3·K-1 with the particle size decreasing from 20~25 mm to 15~20 mm, while that is 3152.65 W·m-3·K-1 with the particle size decreasing from 15~20 mm to 10~15 mm. In addition, the variation of the measured value of the Nusselt number with the Reynolds number has the same trend as predicted values obtained by other works. However, there is a considerable deviation in the value. Among them, the minimum value of the mean relative error is 26.81%. It is proved that the previous empirical correlations are no longer applicable, while the predicted value of this work is in good agreement with the measured value with the mean deviation of only 7.61%. Therefore, the modified correlation can accurately predict the gas-solid heat transfer characteristics in the sinter bed, which lays a foundation for the numerical design and optimization of the new process.